Fostering entrepreneurship: Developing a risk-taking culture in singapore - Balbir B. Bhasin (New England Journal of Entrepreneurship, 2007)
About 10 years ago the Singapore Government realized that entrepreneurial spirit was lacking in its general population. These conclusions were confirmed by an empirical survey, the Global Entrepreneurship Monitor (GEM), an annual assessment of the national level of entrepreneurial activity. The paternalistic and authoritative approach of the government contributed to the general population’s averseness to participating in riskoriented ventures. Removing impediments to entrepreneurship is a key challenge for the government and the business sector if the island republic is to maintain its national competitiveness. This article explores the various initiatives taken by the government to stimulate risk-taking and attempts to ascertain if the various measures can be used as key factors to strengthen the inherent cultural values that stimulate the entrepreneurial spirit.The observations can serve as a useful tool for academics and managers in recognizing the cultural traits that influence and help foster entrepreneurial tendencies.